Polymer processing : modeling and simulation - Osswald, Tim A. (Hanser Publishers, 2006)
This book addresses traditional polymer processing as well as the emerging technologies associated with the plastics industry in the 21st Century, and combines engineering modeling aspects with computer simulation of realistic polymer processes. This book is designed to provide a polymer processing background to engineering students and practicing engineers. This three-part textbook is written for a two-semester polymer processing series in mechanical and chemical engineering. The first and second part of the book are designed for a senior- to graduate level course, introducing polymer processing, and the third part is for a graduate course on simulation in polymer processing. Throughout the book, many applications are presented in form of examples and illustrations. These will also serve the practicing engineer as a guide when determining important parameters and factors during the design process or when optimizing a process. Examples are presented throughout the book, and problems and solutions are available.